Case Study : Perniagaan Naim Gulai Sembilang / Muhammad Amin Hamdan - Hamdan, Muhammad Amin (2020)
NAIM Gulai Sembilang is a local SME company located at Tanjung Dawai, Kedah. This local cooking paste company has a dream to export their products into international markets. Pn. Zarina and En. Ibrahim has felt the struggle at the beginning of business where they start from the bottom until their brand is already met for many people. The original recipe from Pn. Zarina used to produce their own cooking paste from a long time ago until now makes the paste very delicious. For this study, SWOT analysis is applied for the company to identify their strengths, recognize their weaknesses, help the company to expand their products to increase their profits and also to handle all the threats that have come. From these weaknesses, the company could change their weaknesses to strength and find the best solutions to resolve the problems.